Collision-induced absorption in Ar-Xe: a comparative study of empirical and ab initio interaction potentials and electric dipole moments. (December 2022) - Gustafsson, Magnus; El-Kader, M.S.A.
Highlights: Empirical potential energy curves of types Barker-Fisher-Watts and modified Tang-Toennies are developed based on experimental vibrational energies. All pairs in an argon-xenon gas mixture are considered. An empirical dipole curve for an argon-xenon pair is developed based on collision-induced absorption spectral moments. It is compared with state of the art ab initio calculations. The empirical potential curves are tested against previously published experimental transport properties. They are also compared with state of the art ab initio calculations. The empirical dipole and the mixed pair potentials are also tested against experimental collision-induced absorption (CIA) spectra from the literature. We conclude that CIA spectra are more sensitive than the transport properties to small differences in the potential curves. CIA spectra are also highly sensitive to variations in the induced dipole. Abstract: Empirical Barker-Fisher-Watts and modified Tang-Toennies potential energy curves are obtained through fit to experimental vibrational transition energies for argon–argon, xenon–xenon, and argon–xenon pairs. The potentials are tested against experimental thermophysical and transport properties, and agreement is observed. Also, an interaction-induced electric dipole moment curve for the argon–xenon pair is determined through a fit to experimental spectral moments for collision-induced absorption. The argon–xenon potentials and dipole are tested in a complete quantum dynamical calculation of the collision-induced absorption profiles, which can be compared with a laboratory measurement. This provides further analysis of the accuracy of the empirical argon–xenon data, as calculations of absorption profiles are highly sensitive to the input of molecular data.